The Effect of Acid Treatment on Diatomite and Its Application in Treating Semenyih and Langat River Water - Selvaraj K.; Mohd Sidek L.; Tamunaidu P.; Noor M.J.M.M.; Hayder G. (Springer, 2023)
The water quality in the rivers of Malaysia is slowly deteriorating, often, high turbid water intake in water treatment plant causes overloading thus raising water treatment cost. Therefore, this study will provide an insight into the application of acid-treated diatomite in treating turbid river water in Malaysia. The objective of this study is to eliminate the impurities that block the pores through acid treatment and evaluate the performance of acid-treated diatomite in treating turbid river water. The diatomite was treated with 5N sulphuric acid (H2SO4) to remove impurities that block the pore, which will reduce its efficiency to capture the suspended solids and sediment. The river water samples were taken from Semenyih and Langat Rivers flowing from Semenyih and Langat Dams. The variation in natural organic matter in river water samples helps to validate the efficiency of diatomite. The results revealed that the acid-treated diatomite has better turbidity reduction efficiency compared to the untreated diatomite. Turbidity removal efficiency achieved for Semenyih River was 99% with a dosage of 66mg/L at pH of 7.1 whereas for Langat river was 99% with a dosage of 74mg/L at pH of 7.9. On the other hand, untreated diatomite showed turbidity removal efficiency below 20%. These results showed that acid-treated diatomite has the potential to be an effective coagulant to reduce the high turbid water with turbidity efficiency above 90%. 2020, Springer Nature Singapore Pte Ltd.